2020
DOI: 10.3389/fnagi.2020.563559
|View full text |Cite
|
Sign up to set email alerts
|

Association of Subcortical Structural Shapes With Tau, Amyloid, and Cortical Atrophy in Early-Onset and Late-Onset Alzheimer’s Disease

Abstract: The objectives of this study were to compare the topographical subcortical shape and to investigate the effects of tau or amyloid burden on atrophic patterns in early onset Alzheimer's disease (EOAD) and late-onset Alzheimer's disease (LOAD). One hundred and sixty-one participants (53 EOAD, 44 LOAD, 33 young controls, and 31 older controls) underwent [18F]THK5351 positron emission tomography (PET), [18F]flutemetamol (FLUTE) PET, and 3T MRI scans. We used surface-based analysis to evaluate subcortical structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…Those findings are supported by a meta-analysis and review, which also shows that mid-life obesity is related to late-life dementia [44]. previously [20,62,63]. Thus, the final distribution of phosphorylated tau extends beyond the initial site(s) of origin of the disease process.…”
Section: Correlation Between Ad and Obesity Brain Maps In Obese Ad Pa...mentioning
confidence: 62%
“…Those findings are supported by a meta-analysis and review, which also shows that mid-life obesity is related to late-life dementia [44]. previously [20,62,63]. Thus, the final distribution of phosphorylated tau extends beyond the initial site(s) of origin of the disease process.…”
Section: Correlation Between Ad and Obesity Brain Maps In Obese Ad Pa...mentioning
confidence: 62%
“…Voxel-based MRI analysis showed no significant difference in cortical atrophy between EOAD and LOAD in our study. However, most previous ones have reported that cortical atrophy is more extensive in EOAD, although the patterns of atrophy varied 10,22,38,39 . Early-onset AD typically showed more parietal involvement, whereas LOAD was associated with more hippocampus atrophy.…”
Section: Discussionmentioning
confidence: 80%
“…6,8,9 Several studies have reported that EOAD exhibits more severe cortical atrophy, greater reduction in cerebral metabolism, and a higher degree of tau deposition than LOAD. [9][10][11][12][13][14][15] However, because of heterogeneity, heredity, and other factors, imaging features may overlap. 14,16 The impact of age at onset on Aβ deposition is controversial.…”
mentioning
confidence: 99%
“…Additionally, increased ventral posterolateral asymmetry in the thalamus has been noted to be associated with worse cognitive function [12]. These subcortical regions of the brain (i.e., thalamus and putamen) may be impacted earlier in AD [29], when excess Aβ production drives disease progression. One possible explanation could be that significant amyloid burden is interfering with the cortical communication pathway that goes through the subcortical regions like thalamus and putamen.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing question of how disease progression manifests in cortical versus subcortical brain structures [27, 28]. In a longitudinal study, researchers identified significant putamen atrophy and right dominant asymmetry as people age [29].…”
Section: Discussionmentioning
confidence: 99%